Effect of laser scanning speed on TiN/TiB-Ti based composite. (1st June 2013) - Li, M; Huang, J; Zhu, Y Y; Li, Z G; Wu, Y X
<x xml:space="preserve">Abstract</x> In situ synthesised TiN and TiB particulate reinforced metal matrix composite coating was formed on Ti-3Al-2V alloy by laser cladding with a Ti/h-BN powder mixture. The phase structure, microstructure, microhardness and wear performance of the clad layer were analysed by optical microscope, X-ray diffraction, scanning electron microscopy, microhardness tester and wear testing machine. In situ TiN and TiB were synthesised in the forms of equiaxed crystal and needle platelet/whisker type microstructures in the clad layers. The scanning speed plays an important role on the microstructure of the TiN and TiB. The microhardness of laser clad layer was 850-1250 HV0·5, which was about five times of the substrate. The wear height loss of the substrate is almost two times of the clad layers.